Development of Executive Information System to Support Strategic Goals in Retail Company - Willy Johan Widjaja Saputra (Engineering, MAthematics and Computer Science (EMACS) Journal, 2019)
One way to present accurate and actual information to the executive is to use the Executive Information System. The Executive Information System is designed for executives who need information to monitor the situation and manage company management. Problems that may arise at this time are the lack of available information for executives because of geographical barriers, for example the distance between the head ofce and branches that are far apart or executives who often work out of the ofce so that they cannot monitor the company. This is because generally the Executive Information System that exists is only available and can be accessed from within the company environment so executives who are outside the company environment cannot access the Executive Information System to get the information needed. With the existence of an intranet-based Executive Information System, it is expected to cover the shortcomings of the Executive Information System which is not based on intranets. Information needed by executives is not only available in the corporate environment but is also available at a site that can be accessed by executives via the internet, so that executives can easily access information to monitor company performance and determine company management policies even though the executive in question is at outside the corporate environment, especially those related to marketing the company’s products. The system we built proved to be very eﬀective in helping executives to control and monitor the company and make it easier to make decisions regarding company management.